Capital accumulation, dynamic insufficiency and economic growth in Latin America - Avendaño Vargas, Blanca Lilia; Perrotini Hernández, Ignacio (Papeles de Europa, 2017)
In this paper we analyse theoretically and empirically the relationship between dynamic insufficiency (DI) (Prebisch, 1970; Avendaño & Perrotini, 2015) and the growth rate consistent with balance of payments (gbp) equilibrium (Thirlwall, 1979) for a set of Latin American economies during the period 1977-2011. Our hypothesis is that DI exacerbates the external constraint on growth due to the gap between the natural rate of capital accumulation and the guaranteed growth rate (kn>gw) and that there is a causal relationship between and. This means that is determined by demand and supply conditions.
Keywords: Latin America; capital accumulation; balance of payments; endogenous growth